Laser treatment of aluminum composite and investigation of thermal stress field. Issue 9 (October 2016) - Yilbas, B.; Akhtar, S.; Karatas, C.; Ali, H.; Boran, K.; Khaled, M.; Al-Aqeeli, N.; Aleem, A.
Abstract Laser surface melting of hot pressed aluminum composite tile, consisting of 90 % aluminum and 10 % WC, is carried out. Temperature and stress fields developed in the laser-treated region are modeled and predicted using ABAQUS finite element code in line with the experimental conditions. The spiral motion of the laser beam is incorporated at the surface during the laser scanning. This arrangement provides self-annealing effect on the initially formed laser scanning tracks through heat conduction from the lately formed laser scanning tracks. Surface temperature predictions are validated through the thermocouple data. Morphological and metallurgical changes in the laser-treated layer are examined using optical and electron scanning microscopes. It is found that the cooling rates in the central region of the workpiece remain low because of the self-annealing effect of the lately formed laser scanning tracks. This, in turn, lowers von Mises stress levels in this region. Stress peaks are formed below the surface because of the high thermal strain formed in this region during the cooling cycle. The spiral scanning of the laser beam causes oscillating stress levels in the surface region of the laser-treated layer; in which case, its amplitude reduces with the progressing time. Laser-treated layer is free from cracks and crack networks, which is associated with the self-annealing effect of the lately formed laser scanning tracks.